Answer:
B
Step-by-step explanation:
So, we know that this inequality has an "at most" in its phrase, therefore signifying the sign x <em>≤</em> 5. Since the x is in the left side without any negatives, so <em>the arrow goes left, and the circle is filled</em>. So, B.
The first step to solving this is converting these mixed numbers into improper fractions. You would do that by multiplying the denominator by the whole number and adding the numerator to that number; this number replaces the numerator. It would look something like this:
1 8/10 --> 18/10
2 2/5 --> 12/5
Now, to subtract the second fraction from the first one, the denominators of both fractions must be the same. We can make them the same by multiplying the second fraction by 2:
12/5 * 2/2 = 24/10
Now we can set up the equation as:
18/10 - 24/10 = -6/10 --> -3/5
The answer is negative 3/5.
I hope this helps.
Answer:
c
Step-by-step explanation:
Answer:
67
Step-by-step explanation:
4x+3+15x-8=90(complementary angle)
x=5
now D = 15*5-8
d=67
The given expression :
![y=(\frac{1}{2})^x](https://tex.z-dn.net/?f=y%3D%28%5Cfrac%7B1%7D%7B2%7D%29%5Ex)
For coordinates:
put x = 0 then :
![\begin{gathered} y=(\frac{1}{2})^0 \\ y=1 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20y%3D%28%5Cfrac%7B1%7D%7B2%7D%29%5E0%20%5C%5C%20y%3D1%20%5Cend%7Bgathered%7D)
Coordinate : (x, y) = (0, 1)
Put x= 1 and simplify :
![\begin{gathered} y=(\frac{1}{2})^1 \\ y=\frac{1}{2} \\ y=0.5 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20y%3D%28%5Cfrac%7B1%7D%7B2%7D%29%5E1%20%5C%5C%20y%3D%5Cfrac%7B1%7D%7B2%7D%20%5C%5C%20y%3D0.5%20%5Cend%7Bgathered%7D)
Coordinate : (x, y) = ( 1, 0.5)
Put x = (-2) and simplify :
![\begin{gathered} y=(\frac{1}{2})^{-2} \\ y=\frac{1^{-2}}{2^{-2}} \\ y=\frac{2^2}{1^2} \\ y=2^2 \\ y=4 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20y%3D%28%5Cfrac%7B1%7D%7B2%7D%29%5E%7B-2%7D%20%5C%5C%20y%3D%5Cfrac%7B1%5E%7B-2%7D%7D%7B2%5E%7B-2%7D%7D%20%5C%5C%20y%3D%5Cfrac%7B2%5E2%7D%7B1%5E2%7D%20%5C%5C%20y%3D2%5E2%20%5C%5C%20y%3D4%20%5Cend%7Bgathered%7D)
Coordinate : (x, y) = ( -2, 4)
Put x = (-3) and simplify :
![\begin{gathered} y=(\frac{1}{2})^{-3} \\ y=\frac{1^{-3}}{2^{-3}} \\ y=\frac{2^3}{1^3} \\ y=2^3 \\ y=8 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20y%3D%28%5Cfrac%7B1%7D%7B2%7D%29%5E%7B-3%7D%20%5C%5C%20y%3D%5Cfrac%7B1%5E%7B-3%7D%7D%7B2%5E%7B-3%7D%7D%20%5C%5C%20y%3D%5Cfrac%7B2%5E3%7D%7B1%5E3%7D%20%5C%5C%20y%3D2%5E3%20%5C%5C%20y%3D8%20%5Cend%7Bgathered%7D)
Coordinate : (x, y) = (-3, 8)
Substitute x = (-1) and simplify :
![\begin{gathered} y=(\frac{1}{2})^x \\ y=(\frac{1}{2})^{-1} \\ y=\frac{1^{-1}}{2^{-1}} \\ y=\frac{2}{1} \\ y=2 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20y%3D%28%5Cfrac%7B1%7D%7B2%7D%29%5Ex%20%5C%5C%20y%3D%28%5Cfrac%7B1%7D%7B2%7D%29%5E%7B-1%7D%20%5C%5C%20y%3D%5Cfrac%7B1%5E%7B-1%7D%7D%7B2%5E%7B-1%7D%7D%20%5C%5C%20y%3D%5Cfrac%7B2%7D%7B1%7D%20%5C%5C%20y%3D2%20%5Cend%7Bgathered%7D)
Coordinate : (x, y) = ( -1, 2)
So, the coordinates are :
The graph is :